Stakeholders’ vision and global goals for food systems in the Solomon Islands: identifying relevant indicators to track progress - Boylan, Sinead; Brewer, Tom D.; Farrell, Penny; Sharp, Michael K.; Mauli, Senoveva; Tuqa, Alisi; Boydell, Edward; Farmery, Anna K. (Frontiers in Sustainable Food Systems, 2024)
Research on food system framework development has increased substantially in recent years to better understand how we can best transform food systems. However, these frameworks generally take a one-size-fits-all approach, with food system indicators lacking relevance in many countries and territories. This research, centred on the Solomon Islands as a case study, employed a participatory approach involving stakeholders to identify context-specific indicators across three food systems pathways. These pathways, reflecting context-specific goals and a collective vision, encompassed strengthening and connecting rural food systems, enhancing the national policy environment, and advocating for food environments supporting healthy food accessibility, affordability, and convenience. The research identified a range of context-specific indicators and evaluated their alignment with existing data sources. Results underscored the need for data collection and analysis efforts to inform evidence-based decision-making. The study also emphasised the importance of engaging diverse stakeholders to ensure a comprehensive and representative set of indicators, aligning with regional and global efforts to advance food system resilience and sustainability. This research lays the foundation for future endeavours to enhance food system monitoring and assessment, acknowledging nuances and complexities specific to the Solomon Islands and similar contexts.